Chain-type multi-mode polarization-sensitive metamaterial absorber in infrared band - Xinyu Wang; Zhongzhu Liang; Fuming Yang; Xiaoyan Shi; Jinhuan Li; Yongjun Dong; Weizhen Liu; Yan Jia; Wenwen Sun; Zhe Wu; Xiangtao Chen; Siyu Guo (Results in Physics)
Polarized light, abundant in material information, necessitates perfect broadband absorption by metamaterial absorbers across extensive angular ranges for applications in electromagnetic stealth and polarization filtering. Despite the challenges in achieving broadband polarization-sensitive absorption in both the mid-infrared and long-wave infrared spectrums, this paper introduces a novel multi-mode polarization-sensitive infrared metamaterial absorber designed with a chain-type structure. The geometrical parameters of this absorber have been meticulously optimized through parameter tuning and other strategies to maximize absorption efficiency. Notably, the absorber reaches an average absorption of 90.37% for TE polarization in the mid-wave infrared band and 96.68% for TM polarization in the long-wave infrared band. Additionally, it demonstrates a remarkable 95.2% absorption stability across incidence angles from 0 to 60 degrees, showcasing effective polarization performance and a wide response wavelength. This absorber is ideal for use in polarization detection devices, infrared filters, and similar applications.